2015
DOI: 10.3389/fmicb.2015.00398
|View full text |Cite
|
Sign up to set email alerts
|

A novel assay for the detection of bioactive volatiles evaluated by screening of lichen-associated bacteria

Abstract: Volatile organic compounds (VOCs) produced by microorganisms are known both for their effect on pathogens and their role as mediators in various interactions and communications. Previous studies have demonstrated the importance of VOCs for ecosystem functioning as well as their biotechnological potential, but screening for bioactive volatiles remained difficult. We have developed an efficient testing assay that is based on two multi-well plates, separated by a sealing silicone membrane, two tightening clamps, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…Naturally occurring VOCs of endophytic bacteria are regarded as sources of new antifungal agents that are safe for humans and the environment and do not have a harmful influence on the host plants (Gao et al, 2017). Microbial VOCs inhibit the growth of pathogenic fungi; improve plant growth (Park et al, 2015); mediate relationships, interactions, and communications between organisms (Cernava et al, 2015); identify bacterial species; and induce systemic resistance in plants (Zamioudis et al, 2015). GC-MS has revealed that 29 unique VOCs produced by Bacillus velezensis ZSY-1 isolated from Chinese catalpa exhibit significant antifungal activity against plant pathogenic fungi (Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring VOCs of endophytic bacteria are regarded as sources of new antifungal agents that are safe for humans and the environment and do not have a harmful influence on the host plants (Gao et al, 2017). Microbial VOCs inhibit the growth of pathogenic fungi; improve plant growth (Park et al, 2015); mediate relationships, interactions, and communications between organisms (Cernava et al, 2015); identify bacterial species; and induce systemic resistance in plants (Zamioudis et al, 2015). GC-MS has revealed that 29 unique VOCs produced by Bacillus velezensis ZSY-1 isolated from Chinese catalpa exhibit significant antifungal activity against plant pathogenic fungi (Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia and Pseudomonas isolated from lichens exhibit highly effective antagonists of certain bacterial and fungal pathogens (Cernava et al . ,b). Thus, an essential role of this bacterial fraction in pathogen defence and microbial community stabilization is envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of volatile compounds from bacteria was performed according to the methods published by Verginer et al . and Cernava et al . In brief, 8 mL of autoclaved rapeseed meal agar was poured into a 20‐mL headspace vial, which was positioned at a slope to increase the surface of the agar.…”
Section: Methodsmentioning
confidence: 99%